What can we conclude about organic matter by tracing metal reduction/oxidation in natural water samples using voltammetric methods? - Louis, Y.; Nicolau, R.; Mounier, S.; Omanovic, D.; Pizeta, I. (2005)
Voltammetric methods are sensitive enough to detect certain metals (Zn, Cd, Pb, Cu, but also Mn, Fe, Hg,..- depending of the electrode used and the method applied), without any pretreatment of the natural water sample. Using a knowledge and experience of the model compositions of water samples containing known ligands, it is possible to characterize a natural sample proposing some of the properties of the naturally occurring ligands. A water sample taken at the estuary of the little French Mediterranean river Eygoutier is analysed applying differential pulse anodic stripping voltammetry in a repetitive way in order to obtain pseudopolarograms of all detected metals. Differences of those pseudopolarograms regarding the various treatment of the sample (filtering, acidifying, microwave digesting, addition of metal ions) bear information about the ligands present in the solution, their interaction with metals in term of complex stability. In combination with other analytical methods, one can obtain better insight in natural organic matter (NOM) behaviour in natural and polluted waters. As a consequence, these results could lead to better modelling of NOM alone and in interaction with metal ions.